Electrocoagulation Technique for the Treatment of Effluents from Metal Working Fluid - K.V.Radha (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
Using mild steel, electrocoagulation is a successful method for treating Metal Working Fluid (MWF) industrial effluent. The goal of the current study is to determine how electrolysis time, applied charge density, and electrolyte pH affect the effectiveness of electrocoagulation in treating MWF effluent. According to the current experimental findings, electrocoagulation is an excellent method for treating wastewater. The electrolysis time of 55-60 minutes, for a current density of 3 A/dm3 and pH 7 at a temperature of 350C effective treatment of the effluent was observed. It was found that the highest COD and color removals were 95% and 98%, respectively. Several adsorption isotherms were used to describe the electrocoagulation process, and it was shown that the predictions of the Langmuir isotherm models agree well with the experimental findings. Langmuir isotherm models (R²>0.99) provided a better fit than Freundlich models for the electrocoagulation process.